Effects Of Discounts, Brand Image And In-Store Display Against Impulsive Buying In Fashion Products At Matahari Department Store Bengkulu - Annisa Janur NZ.; Muhartini Salim; Sularsih Anggarawati (The Manager Review, 2023)
The purpose of this study is to analyze the effect of the discount, brand image and in-store display toward impulsive buying at the Matahari Department Store in the Bengkulu City. The data used in this research is the primary data obtained from the questionnaire to the dissemination of the results of the customers of the Matahari Department Store in the Bengkulu City. The sample used in the analysis was 185 respondents. Data analysis method used is descriptive analysis and multiple linear regression analysis. From hypothesis testing retrieved results: first, the discount variable has a positive significant effect on impulsive buying. Its means are, if the discount is good, will be increasing of customers to impulsive buying. Second, the brand image variable has positive and significant effect on impulsive buying. Its means are, if the brand image is good, will be increasing of customers to impulsive buying. Third the in-store display variable has positive and significant effect on impulsive buying. Its means are, if the in-store is good, will be increasing of customers to impulsive buying. Keywords: Discount, Brand image, In-store display and Impulsive buying